Proceedings of the 3rd IPLeiria's International Health Congress. Issue 3 (July 2016) - Tomás, Catarina; Oliveira, Emanuel; Sousa, D.; Uba-Chupel, M.; Furtado, G.; Rocha, C.; Teixeira, A.; Ferreira, P.; Alves, Celeste; Gisin, Stefan; Catarino, Elisabete; Carvalho, Nelma; et al.
Table of contents S1 Health literacy and health education in adolescence Catarina Cardoso Tomás S2 The effect of a walking program on the quality of life and well-being of people with schizophrenia Emanuel Oliveira, D. Sousa, M. Uba-Chupel, G. Furtado, C. Rocha, A. Teixeira, P. Ferreira S3 Diagnosis and innovative treatments - the way to a better medical practice Celeste Alves S4 Simulation-based learning and how it is a high contribution Stefan Gisin S5 Formative research about acceptability, utilization and promotion of a home fortification programme with micronutrient powders (MNP) in the Autonomous Region of Príncipe, São Tomé and Príncipe Elisabete Catarino, Nelma Carvalho, Tiago Coucelo, Luís Bonfim, Carina Silva S6 Safety culture of the patient: a reflexion about the therapeutic approach on the patient with vocal pathology Débora Franco S7 About wine, fortune cookies and patient experience Jesús Alcoba González O1 The psychological impact on the emergency crews after the disaster event on February 20, 2010 Helena G. Jardim, Rita Silva O2 Musculoskeletal disorders in midwives Cristina L. Baixinho, Mª Helena Presado, Mª Fátima Marques, Mário E. Cardoso O3 Negative childhood experiences and fears of compassion: Implications for psychological difficulties in adolescence Marina Cunha, Joana Mendes, Ana Xavier, Ana Galhardo, Margarida Couto O4 Optimal age to give the first dose of measles vaccine in Portugal João G. Frade, Carla Nunes, João R. Mesquita, Maria S. Nascimento, Guilherme Gonçalves O5 Functional assessment of elderly in primary care Conceição Castro, Alice Mártires, Mª João Monteiro, Conceição Rainho O6 Smoking and coronary events in a population of Spanish health-care centre: An observational study Francisco P. Caballero, Fatima M. Monago, Jose T. Guerrero, Rocio M. Monago, Africa P. Trigo, Milagros L. Gutierrez, Gemma M. Milanés, Mercedes G. Reina, Ana G. Villanueva, Ana S. Piñero, Isabel R. Aliseda, Francisco B. Ramirez O7 Prevalence of musculoskeletal injuries in Portuguese musicians Andrea Ribeiro, Ana Quelhas, Conceição Manso O8 Hip fractures, psychotropic drug consumption and comorbidity in patients of a primary care practice in Spain Francisco P. Caballero, Jose T. Guerrero, Fatima M. Monago, Rafael B. Santos, Nuria R. Jimenez, Cristina G. Nuñez, Inmaculada R. Gomez, Mª Jose L. Fernandez, Laura A. Marquez, Ana L. Moreno, Mª Jesus Tena Huertas, Francisco B. Ramirez O9 The role of self-criticism and shame in social anxiety in a clinical SAD sample Daniel Seabra, Mª Céu Salvador O10 Obstruction and infiltration: a proposal of a quality indicator Luciene Braga, Pedro Parreira, Anabela Salgueiro-Oliveira, Cristina Arreguy-Sena, Bibiana F. Oliveira, Mª Adriana Henriques O11 Balance and anxiety and depression symptoms in old age people Joana Santos, Sara Lebre, Alda Marques O12 Prevalence of postural changes and risk factors in school children and adolescents in a northern region (Porto) Clarinda Festas, Sandra Rodrigues, Andrea Ribeiro, José Lumini O13 Ischemic stroke vs. haemorrhagic stroke survival rate Ana G. Figueiredo O14 Chronobiological factors as responsible for the appearance of locomotor pathology in adolescents Francisco J. Hernandez-Martinez, Liliana Campi, Mª Pino Quintana-Montesdeoca, Juan F. Jimenez-Diaz, Bienvenida C. Rodriguez-De-Vera O15 Risk of malnutrition in the elderly of Bragança Alexandra Parente, Mª Augusta Mata, Ana Mª Pereira, Adília Fernandes, Manuel Brás O16 A Lifestyle Educational Programme for primary care diabetic patients: the design of a complex nursing intervention Mª Rosário Pinto, Pedro Parreira, Marta L. Basto, Ana C. Rei, Lisete M. Mónico O17 Medication adherence in elderly people Gilberta Sousa, Clementina Morna, Otília Freitas, Gregório Freitas, Ana Jardim, Rita Vasconcelos O18 Hospitalization for cervical cancer of residents in the metropolitan region of Porto Alegre, Southern Brazil, 2012 to 2014 Lina G. Horta, Roger S. Rosa, Luís F. Kranz, Rita C. Nugem, Mariana S. Siqueira, Ronaldo Bordin O19 Oncologic assistance of high complexity: evaluation of regulating accesses Rosiane Kniess, Josimari T. Lacerda O20 Perceived barriers for using health care services by the older population as seen by the social sector: findings from the Vila Nova de Gaia Gerontological Plan Joana Guedes, Idalina Machado, Sidalina Almeida, Adriano Zilhão, Helder Alves, Óscar Ribeiro O21 Sleep difficulties and depressive symptoms in college students Ana P. Amaral, Ana Santos, Joana Monteiro, Mª Clara Rocha, Rui Cruz O22 Psychopathological symptoms and medication use in higher education Ana P. Amaral, Marina Lourenço, Mª Clara Rocha, Rui Cruz O23 Sexually transmitted diseases in higher education institutions Sandra Antunes, Verónica Mendonça, Isabel Andrade, Nádia Osório, Ana Valado, Armando Caseiro, António Gabriel, Anabela C. Martins, Fernando Mendes O24 Alcohol consumption and suicide ideation in higher education students Lídia Cabral, Manuela Ferreira, Amadeu Gonçalves O25 Quality of life in university students Tatiana D. Luz, Leonardo Luz, Raul Martins O26 Male and female adolescent antisocial behaviour: characterizing vulnerabilities in a Portuguese sample Alice Morgado, Maria L. Vale-Dias O27 Risk factors for mental health in higher education students of health sciences Rui Porta-Nova O28 International classification of functioning disability and health as reflexive reasoning in primary attention in health Tânia C. Fleig, Éboni M. Reuter, Miriam B. Froemming, Sabrina L. Guerreiro, Lisiane L. Carvalho O29 Risk factors and cardiovascular disease in Portalegre Daniel Guedelha, P. Coelho, A. Pereira O30 Health status of the elderly population living in Portalegre historic city centre: A longitudinal study António Calha, Raul Cordeiro O31 Student's sleep in higher education: sleep quality among students of the IPB Ana Gonçalves, Ana Certo, Ana Galvão, Mª Augusta Mata O32 Trend in mortality from cervical cancer in the metropolitan area of Florianópolis, state of Santa Catarina, Brazil, 2000 to 2013 Aline Welter, Elayne Pereira, Sandra Ribeiro, Marcia Kretzer O33 Adherence to treatment in the elderly in an urban environment in Spain Juan-Fernando Jiménez-Díaz, Carla Jiménez-Rodríguez, Francisco-José Hernández-Martínez, Bienvenida-Del-Carmen Rodríguez-De-Vera, Alexandre Marques-Rodrigues O34 Beira Baixa Blood Pressure Study (Study PABB) Patrícia Coelho, Tiago Bernardes, Alexandre Pereira O35 Trends in cervical cancer mortality statistics in Santa Catarina State, Brazil, by age group and macro-region, from 2000 to 2013 Patrícia Sousa, João G. Filho, Nazare Nazario, Marcia Kretzer O36 Sleep problems among Portuguese adolescents: a public health issue Odete Amaral, António Garrido, Nélio Veiga, Carla Nunes, Ana R. Pedro, Carlos Pereira O37 Association between body fat and health-related quality of life in patients with type 2 diabetes António Almeia, Helder M. Fernandes, Carlos Vasconcelos, Nelson Sousa, Victor M. Reis, M. João Monteiro, Romeu Mendes O38 Therapy adherence and polypharmacy in non-institutionalized elderly from Amares county, Portugal Isabel C. Pinto, Tânia Pires, João Gama O39 Prevalence of surgical site infection in adults at a hospital unit in the North of Portugal Vera Preto, Norberto Silva, Carlos Magalhães, Matilde Martins O40 Frailty phenotype in old age: implications to intervention Mafalda Duarte, Constança Paúl, Ignácio Martín O41 Portuguese women: sexual symptoms in perimenopause Arminda A. Pinheiro O42 Predictive ability of the Perinatal Depression Screening and Prevention Tool – preliminary results of the categorical approach Sandra Xavier, Julieta Azevedo, Elisabete Bento, Cristiana Marques, Mariana Marques, António Macedo, Ana T. Pereira O43 Aging and muscle strength in patients with type 2 diabetes: cross sectional analysis José P. Almeida, António Almeida, Josiane Alves, Nelson Sousa, Francisco Saavedra, Romeu Mendes O44 Accessibility of the elderly in the prevention of hypertension in a family health unit Ana S. Maia, Michelle T. Oliveira, Anderson R. Sousa, Paulo P. Ferreira, Luci S. Lopes, Eujcely C. Santiago O45 Community Health screenings and self-reported chronic diseases Sílvia Monteiro, Ângelo Jesus, Armanda Colaço, António Carvalho, Rita P. Silva, Agostinho Cruz O46 Evaluation of indoor air quality in Kindergartens Ana Ferreira, Catarina Marques, João P. Figueiredo, Susana Paixão O47 Atmospheric exposure to chemical agents under the occupational activity of pathology technicians Ana Ferreira, Carla Lopes, Fernando Moreira, João P. Figueiredo O48 Occupational exposure to air pollutants in night entertainment venues workers Ana Ferreira, Diana Ribeiro, Fernando Moreira, João P. Figueiredo, Susana Paixão O49 Beliefs and attitudes of young people towards breastfeeding Telma Fernandes, Diogo Amado, Jéssica Leal, Marcelo Azevedo, Sónia Ramalho O50 Profiling informal caregivers: surveying needs in the care of the elderly Catarina Mangas, Jaime Ribeiro, Rita Gonçalves O51 Visual health in teenagers Amélia F Nunes, Ana R. Tuna, Carlos R. Martins, Henriqueta D. Forte O52 Amenable mortality and the geographic accessibility to healthcare in Portugal Cláudia Costa, José A. Tenedório, Paula Santana O53 Bacterial contamination of door handles in a São Paulo See Metropolitan Cathedral public restrooms in Brazil J. A. Andrade, J. L. Pinto, C. Campofiorito, S. Nunes, A. Carmo, A. Kaliniczenco, B. Alves, F. Mendes, C. Jesus, F. Fonseca, F. Gehrke O54 Adherence of patients to rehabilitation programmes Carlos Albuquerque, Rita Batista, Madalena Cunha, António Madureira, Olivério Ribeiro, Rosa Martins O55 Prevalence of malnutrition among Portuguese elderly living in nursing homes: preliminary results of the PEN-3S project Teresa Madeira, Catarina Peixoto-Plácido, Nuno Santos, Osvaldo Santos, Astrid Bergland, Asta Bye, Carla Lopes, Violeta Alarcão, Beatriz Goulão, Nuno Mendonça, Paulo Nicola, João G. Clara O56 Relation between emotional intelligence and mental illness in health students João Gomes, Ana Querido, Catarina Tomás, Daniel Carvalho, Marina Cordeiro P1 Fall risk factors in people older than 50 years old – a pilot report Marlene C. Rosa, Alda Marques P2 What about the Portuguese oldest old? A global overview using census data Daniela Brandão, Óscar Ribeiro, Lia Araújo, Constança Paúl P3 Prevalence of injuries in senior amateur volleyball athletes in Alentejo and Algarve clubs, Portugal: factors associated Beatriz Minghelli, Sylvina Richaud P4 Shame feelings and quality of life: the role of acceptance and decentring Ana L. Mendes, Joana Marta-Simões, Inês A. Trindade, Cláudia Ferreira P5 Assessment of social support during deployment in portuguese colonial war veterans Teresa Carvalho, Marina Cunha, José Pinto-Gouveia P6 Hospitalization for acute viral bronchiolitis of residents in the metropolitan region of Porto Alegre, Southern Brazil, 2012 to 2014 Morgana C. Fernandes, Roger S. Rosa, Rita C. Nugem, Luís F. Kranz, Mariana S. Siqueira, Ronaldo Bordin P7 Falls-risk screening – an opportunity for preventing falls in the elderly from Nordeste Anabela C. Martins, Anabela Medeiros, Rafaela Pimentel, Andreia Fernandes, Carlos Mendonça, Isabel Andrade, Susana Andrade, Ruth L. Menezes P8 Aging provokes chronodisruption in mature people in temperature circadian rhythm Rafael Bravo, Marta Miranda, Lierni Ugartemendia, José Mª Tena, Francisco L. Pérez-Caballero, Lorena Fuentes-Broto, Ana B. Rodríguez, Barriga Carmen P9 The influence of climate and pollution factors in dengue cases of great ABC region, São Paulo M. A. Carneiro, J. N. Domingues, S. Paixão, J. Figueiredo, V. B. Nascimento, C. Jesus, F Mendes, F. Gehrke, B. Alves, L. Azzalis, F. Fonseca P10 Visual function and impact of visual therapy in children with learning disabilities: a pilot study Ana R. Martins, Amélia Nunes, Arminda Jorge P11 Edentulism and the need of oral rehabilitation among institutionalized elderly Nélio Veiga, Ana Amorim, André Silva, Liliana Martinho, Luís Monteiro, Rafael Silva, Carina Coelho, Odete Amaral, Inês Coelho, Carlos Pereira, André Correia P12 Therapy adherence of outpatients in the pharmacy services of a hospital unit Diana Rodrigues, Nídia Marante, Pedro Silva, Sara Carvalho, André Rts Araujo, Maximiano Ribeiro, Paula Coutinho, Sandra Ventura, Fátima Roque P13 Universal access and comprehensive care of oral health: an availability study Cristina Calvo, Manoela Reses P14 Is the respiratory function of children a predictor of air quality? Coimbra as a case study Jorge Conde, Ana Ferreira, João Figueiredo P15 Meaning-in-life of college students David Silva, Luís Seiça, Raquel Soares, Ricardo Mourão, Teresa Kraus O57 Training needs for nurses in palliative care Ana C. Abreu, José M. Padilha, Júlia M. Alves O58 Impact of computerized information systems in the global nurses' workload: nurses' perceptions and real-time Paulino Sousa, Manuel Oliveira, Joana Sousa O59 The perspective of health care professionals on self-care in hereditary neurodegenerative disease: a qualitative study Sónia Novais, Felismina Mendes O60 Contribution for health-related physical fitness reference values in healthy adolescents Joana Pinto, Joana Cruz, Alda Marques School of Health Sciences, University of Aveiro, 3810-193 Aveiro, Portugal O61 Perception of learning, satisfaction and self-efficacy of nursing students about High-Fidelity Simulation Hugo Duarte, Maria Dos Anjos Dixe, Pedro Sousa O62 Analysis of statements of diagnosis about health deviation in self-care requisites customized in a Nursing Practice Support System (SAPE®): Management of therapeutic regimen Inês Cruz, Fernanda Bastos, Filipe Pereira O63 Hybrid management and hospital governance: doctors and nurses as managers Francisco L. Carvalho, Teresa T. Oliveira, Vítor R. Raposo O64 Time management in health professionals Conceição Rainho, José C. Ribeiro, Isabel Barroso, Vítor Rodrigues O65 Financial rewards and wellbeing in primary health care Carmo Neves, Teresa C. Oliveira O66 Patient safety promotion in the operating room Bárbara Oliveira, Mª Carminda Morais, Pilar Baylina O67 Difficulties and needs of pre-graduate nursing students in the area of Geriatrics/Gerontology Rogério Rodrigues, Zaida Azeredo, Corália Vicente O68 Teaching and learning sexuality in nursing education Hélia Dias, Margarida Sim-Sim O69 Entrepreneurial Motivations Questionnaire: AFC and CFA in academy Pedro Parreira, Anabela Salgueiro-Oliveira, Amélia Castilho, Rosa Melo, João Graveto, José Gomes, Marina Vaquinhas, Carla Carvalho, Lisete Mónico, Nuno Brito O70 Nursing intervention to patient with Permanent Pacemakers and Implantable Cardioverter Defibrillators: a qualitative analysis Cassilda Sarroeira, José Amendoeira, Fátima Cunha, Anabela Cândido, Patrícia Fernandes, Helena R. Silva, Elsa Silva O71 Alcohol consumption among nursing students: where does education fail? Isabel Barroso, Leila Lapa, Cristina Antunes O72 Labour stress in nursing Ana Gonçalves, Ana Galvão, Mª José Gomes, Susana R. Escanciano O73 The influence of safe staff nursing in patient satisfaction with nursing care Maria Freitas, Pedro Parreira, João Marôco O74 Intention to use eHealth strategies with nursing students Ana R. Fernandes, Cremilde Cabral, Samuel Alves, Pedro Sousa O75 Community Based Mental Health: contributions of an interdisciplinary international program for students in higher health education António Ferreira, Fernanda Príncipe, Ulla-Maija Seppänen, Margarida Ferreira, Maribel Carvalhais, Marilene Silva O76 Study of satisfaction at work of graduates in nursing: 2002-2014 Manuela Ferreira, Joana Silva, Jéssica Neves, Diana Costa, Bruno Santos, Soraia Duarte O77 Health professionals' attitudes towards breastfeeding Sílvia Marques, Sónia Ramalho, Isabel Mendes O78 Continuity of nursing care to person with type 2 diabetes Clarisse Louro, Eva Menino, Maria Dixe, Sara S. Dias O79 Stigma toward mental illness among future health professionals Marina Cordeiro, Catarina Tomás, Ana Querido, Daniel Carvalho, João Gomes O80 Working with fears and anxieties of medical students in search of a humanized care Frederico C. Valim, Joyce O. Costa, Lúcia G. Bernardes P16 Surgical paediatrics patients' psycho prophylaxis at a teaching hospital Helena Prebianchi P17 Patient-perceived outcomes in physiotherapy – a pilot study Marlene Cristina Rosa P18 Building competencies for managers in nursing Narcisa Gonçalves, Maria M. Martins, Paulina Kurcgant P19 Theoretical basis underlying physiotherapy practice in stroke rehabilitation André Vieira P20 When the life-cycle ends: the nurse's confrontation with death Sandrina Bento, Sérgio Deodato, Isabel Rabiais P21 Nursing students' opinion about the supervision relationship during their first clinical experience Laura Reis P22 Nursing Relational Laboratory: Pedagogical, dialogic and critical project Ana Torres, Sérgio Soares, Margarida Ferreira, Pedro Graça P23 Job satisfaction of bioscientists at a Lisbon hospital Céu Leitão, Renato Abreu, Fernando Bellém, Ana Almeida, Edna Ribeiro-Varandas, Ana Tavares P24 Sociodemographic and professional profile of nurses and its relation with the importance of family in nursing practices João G. Frade, Carolina Henriques, Eva Menino, Clarisse Louro, Célia Jordão P25 Professional satisfaction of rehabilitation nurses Sofia Neco, Carminda Morais, Pedro Ferreira P26 The person living with a stoma: the formalization of knowledge in nursing Carla R. Silva, Alice Brito, Antónia Silva P27 Validation of the Portuguese versions of the nursing students' perceptions of learning and learner satisfaction with simulation tool Hugo Duarte, Maria Dos Anjos Dixe, Pedro Sousa P28 Physiotherapists' perceived knowledge on technologies for electronic health records for physiotherapy Gabriela Postolache, Raul Oliveira, Isabel Moreira, Luísa Pedro, Sónia Vicente, Samuel Domingos, Octavian Postolache P29 Quality of life and physical activity of medicine undergraduate students in the University of Southern Santa Catarina, Brazil Darlen Silva, João G. Filho, Nazare Nazario, Marcia Kretzer, Dulcineia Schneider P30 The curricular skills for decision making education in a Nursing Degree Fátima M. Marques P31 Effect of nurses' mobilization in satisfaction at work and turnover: An empirical study in the hospital setting Pedro Parreira, Carla Carvalho, Lisete M. Mónico, Carlos Pinto, Sara Vicente, São João Breda P32 Entrepreneurial skills of students of polytechnic higher education in Portugal: Business influences José H. Gomes, Rosa Melo, Pedro Parreira, Anabela Salgueiro, João Graveto, Marina Vaquinhas, Amélia Castilho P33 Design and assessment of e-learning modules for Pharmacology Ângelo Jesus, Nuno Duarte, José C. Lopes, Hélder Nunes, Agostinho Cruz P34 Perspective of nurses involved in an action-research study on the changes observed in care provision: results from a focus group Anabela Salgueiro-Oliveira, Pedro Parreira, Marta L. Basto, Luciene M. Braga P35 Use of peer feedback by nursing students during clinical training: teacher's perception António Ferreira, Beatriz Araújo, José M. Alves, Margarida Ferreira, Maribel Carvalhais, Marilene Silva, Sónia Novais P36 What's new on endotracheal suctioning recommendations Ana S. Sousa, Cândida Ferrito P37 Assessment of the nurses satisfaction on the Central Region of Portugal Pedro L. Ferreira, Alexandre Rodrigues, Margarida Ferreira, Isabel Oliveira P38 Study of graduate's satisfaction with the school of nursing Manuela Ferreira, Jéssica Neves, Diana Costa, Soraia Duarte, Joana Silva, Bruno Santos P39 Partnership between the school of nursing and the hospital: Supervisors´ perspectives Cristina Martins, Ana P. Macedo, Odete Araújo, Cláudia Augusto, Fátima Braga, Lisa Gomes, Maria A. Silva, Rafaela Rosário P40 Coping strategies of college students Luís Pimenta, Diana Carreira, Patrícia Teles, Teresa Barros P41 Emotional intelligence and mental health stigma in health students Catarina Tomás, Ana Querido, Daniel Carvalho, João Gomes, Marina Cordeiro P42 Stigma of mental health assessment: Comparison between health courses Daniel Carvalho, Ana Querido, Catarina Tomás, João Gomes, Marina Cordeiro O81 Short- and long-term effects of pulmonary rehabilitation in mild COPD Cristina Jácome, Alda Marques O82 Phonological awareness programme for preschool children Sylvie Capelas, Andreia Hall, Dina Alves, Marisa Lousada O83 REforma ATIVA: An efficient health promotion program to be implemented during retirement Mª Helena Loureiro, Ana Camarneiro, Margarida Silva, Aida Mendes, Ana Pedreiro O84 Intervention for men who batter women, a case report Anne G.Silva, Elza S. Coelho O85 Immediate effects of Bowen Therapy on muscle tone and flexibility Flávio Melo, Fernando Ribeiro, Rui Torres, Rui Costa O86 Predictive equation for incremental shuttle walk test in adolescents Tânia Pinho, Cristina Jácome, Alda Marques O87 Life satisfaction and psychopathology in institutionalized elderly people: The results of an adapted Mindfulness-Based Stress Reduction program Bárbara Cruz, Daniel Seabra, Diogo Carreira, Maria Ventura O88 Outcome changes in COPD rehabilitation: exploring the relationship between physical activity and health-related outcomes Joana Cruz, Dina Brooks, Alda Marques O89 Assessing the effectiveness of a Complex Nursing Intervention M Rosário Pinto, Pedro Parreira, Marta Lima-Basto, Miguel Neves, Lisete M. Mónico O90 Psychotherapeutic intervention in addiction disorders: Change in psychopathological symptoms and emotional states Carla Bizarro, Marina Cunha, Ana Galhardo, Couto Margarida, Ana P. Amorim, Eduardo Silva O91 Economic impact of a nursing intervention program to promote self-management in COPD Susana Cruz, José M. Padilha, Jorge Valente O92 Multimodal acute pain management during uterine artery embolization in treatment of uterine myomas José T. Guerrero, Francisco P. Caballero, Rafael B. Santos, Estefania P. Gonzalez, Fátima M. Monago, Lierni U. Ugalde, Marta M. Vélez, Maria J. Tena O93 Fluid administration strategies in major surgery: Goal-directed therapy José T. Guerrero, Rafael Bravo, Francisco L. Pérez-Caballero, Isabel A. Becerra, Mª Elizabeth Agudelo, Guadalupe Acedo, Roberto Bajo O94 Development and implementation of a self-management educational programme using lay-led's in adolescents Spina Bifida: A pilot study Isabel Malheiro, Filomena Gaspar, Luísa Barros O95 Influence of chair-based yoga exercises on salivary anti-microbial proteins in institutionalized frail-elderly women: a preliminary study Guilherme Furtado, Mateus Uba-Chupel, Mariana Marques, Luís Rama, Margarida Braga, José P. Ferreira, Ana Mª Teixeira O96 High intensity interval training vs moderate intensity continuous training impact on diabetes 2 João Cruz, Tiago Barbosa, Ângela Simões, Luís Coelho O97 Family caregiver of people with pressure ulcer: Nursing intervention plan Alexandre Rodrigues, Juan-Fernando Jiménez-Díaz, Francisco Martinez-Hernández, Bienvenida Rodriguez-De-Vera, Pedro Ferreira, Alexandrina Rodrigues O98 Chronic effects of exercise on motor memory consolidation in elderly people André Ramalho, João Petrica, Pedro Mendes, João Serrano, Inês Santo, António Rosado O99 Impression cytology of the ocular surface: Collection technique and sample processing Paula Mendonça, Kátia Freitas O100 Does sport practice affect the reaction time in neuromuscular activity? Dora Ferreira, António Brito, Renato Fernandes O101 Efficiency of the enteral administration of fibbers in the treatment of chronic obstipation Sofia Gomes, Fernando Moreira, Cláudia Pinho, Rita Oliveira, Ana I. Oliveira O102 Fast decalcifier in compact bone and spongy bone Paula Mendonça, Ana P. Casimiro, Patrícia Martins, Iryna Silva O103 Health promotion in the elderly – Intervention project in dementia Diana Evangelista O104 Prevention of musculoskeletal disorders through an exercise protocol held in labour context Catarina Leitão, Fábia Velosa, Nélio Carecho, Luís Coelho O105 Knowledge of teachers and other education agents on diabetes type 1: Effectiveness of an intervention program Eva Menino, Anjos Dixe, Helena Catarino, Fátima Soares, Ester Gama, Clementina Gordo O106 Treatment of diabetic peripheral neuropathic pain: a systematic review of clinical trials of phase II and III Eliana Moreira, Cristiana Midões, Marlene Santos O107 New drugs for osteoporosis treatment: Systematic review of clinical trials of phase II and III Sara Machado, Vânia P. Oliveira, Marlene Santos O108 Promoting hope at the end of life: Effectiveness of an Intervention Programme Ana Querido, Anjos Dixe, Rita Marques, Zaida Charepe P43 Psychomotor therapy effects on adaptive behaviour and motor proficiency of adults with intellectual disability Ana Antunes, Sofia Santos P44 The effect of exercise therapy in multiple sclerosis – a single study case Marlene C. Rosa P45 Physical condition and self-efficacy in people with fall risk – a preliminary study Marlene C. Rosa, Silvana F. Marques P46 Shock waves: their effectiveness in improving the symptoms of calcifying tendinitis of the shoulder Beatriz Minghelli, Eulália Caro P47 Pacifier – construction and pilot application of a parenting intervention for parents of babies until six months in primary health care Mª José Luís, Teresa Brandão P48 The influence of Motor Imagery in fine motor skills of individuals with disabilities Pedro Mendes, Daniel Marinho, João Petrica, Diogo Monteiro, Rui Paulo, João Serrano, Inês Santo P49 Evaluation of the effects of a walking programme on the fall risk factors in older people – a longitudinal pilot study Lina Monteiro, Fátima Ramalho, Rita Santos-Rocha, Sónia Morgado, Teresa Bento P50 Nursing intervention programme in lifestyles of adolescents Gilberta Sousa, Otília Freitas, Isabel Silva, Gregório Freitas, Clementina Morna, Rita Vasconcelos P51 The person submitted to hip replacement rehabilitation, at home Tatiana Azevedo, Salete Soares, Jacinta Pisco P52 Effects of Melatonin use in the treatment of neurovegetative diseases Paulo P. Ferreira, Efrain O. Olszewer, Michelle T. Oliveira, Anderson R. Sousa, Ana S. Maia, Sebastião T. Oliveira P53 Review of Phytotherapy and other natural substances in alcohol abuse and alcoholism Erica Santos, Ana I. Oliveira, Carla Maia, Fernando Moreira, Joana Santos, Maria F. Mendes, Rita F. Oliveira, Cláudia Pinho P54 Dietary programme impact on biochemical markers in diabetics: systematic review Eduarda Barreira, Ana Pereira, Josiana A. Vaz, André Novo P55 Biological approaches to knee osteoarthritis: platelet-rich plasma and hyaluronic acid Luís D. Silva, Bruno Maia, Eduardo Ferreira, Filipa Pires, Renato Andrade, Luís Camarinha P56 Platelet-rich plasma and hyaluronic acid intra-articular injections for the treatment of ankle osteoarthritis Luís D. Silva, Bruno Maia, Eduardo Ferreira, Filipa Pires, Renato Andrade, Luís Camarinha P57 The impact of preventive measures in the incidence of diabetic foot ulcers: a systematic review Ana F. César, Mariana Poço, David Ventura, Raquel Loura, Pedro Gomes, Catarina Gomes, Cláudia Silva, Elsa Melo, João Lindo P58 Dating violence among young adolescents Joana Domingos, Zaida Mendes, Susana Poeta, Tiago Carvalho, Catarina Tomás, Helena Catarino, Mª Anjos Dixe P59 Physical activity and motor memory in pedal dexterity André Ramalho, António Rosado, Pedro Mendes, Rui Paulo, Inês Garcia, João Petrica P60 The effects of whole body vibration on the electromyographic activity of thigh muscles Sandra Rodrigues, Rui Meneses, Carlos Afonso, Luís Faria, Adérito Seixas P61 Mental health promotion in the workplace Marina Cordeiro, Paulo Granjo, José C. Gomes P62 Influence of physical exercise on the self-perception of body image in elderly women: A systematic review of qualitative studies Nelba R. Souza, Guilherme E. Furtado, Saulo V. Rocha, Paula Silva, Joana Carvalho O109 Psychometric properties of the Portuguese version of the Éxamen Geronto-Psychomoteur (P-EGP) Marina Ana Morais, Sofia Santos, Paula Lebre, Ana Antunes O110 Symptoms of depression in the elderly population of Portugal, Spain and Italy António Calha O111 Emotion regulation strategies and psychopathology symptoms: A comparison between adolescents with and without deliberate self-harm Ana Xavier, Marina Cunha, José Pinto-Gouveia O112 Prevalence of physical disability in people with leprosy Liana Alencar, Madalena Cunha, António Madureira O113 Quality of life and self-esteem in type 1 and type 2 diabetes mellitus patients Ilda Cardoso, Ana Galhardo, Fernanda Daniel, Vítor Rodrigues O114 Cross-cultural comparison of gross motor coordination in children from Brazil and Portugal Leonardo Luz, Tatiana Luz, Maurício R. Ramos, Dayse C. Medeiros, Bruno M. Carmo, André Seabra, Cristina Padez, Manuel C. Silva O115 Electrocardiographic differences between African and Caucasian people António Rodrigues, Patrícia Coelho, Alexandre Coelho O116 Factors associated with domestic, sexual and other types of violence in the city of Palhoça - Brazil Madson Caminha, Filipe Matheus, Elenice Mendes, Jony Correia, Marcia Kretzer O117 Tinnitus prevalence study of users of a hospital of public management - Spain Francisco J. Hernandez-Martinez, Juan F. Jimenez-Diaz, Bienvendida C. Rodriguez-De-Vera, Carla Jimenez-Rodriguez, Yadira Armas-Gonzalez O118 Difficulties experienced by parents of children with diabetes mellitus of preschool age in therapeutic and nutritional management Cátia Rodrigues, Rosa Pedroso O119 E-mental health - "nice to have" or "must have"? Exploring the attitudes towards e-mental health in the general population Jennifer Apolinário-Hagen, Viktor Vehreschild O120 Violence against children and adolescents and the role of health professionals: Knowing how to identify and care Milene Veloso, Celina Magalhães, Isabel Cabral, Maira Ferraz O121 Marital violence. A study in the Algarve population Filipe Nave, Emília Costa, Filomena Matos, José Pacheco O122 Clinical factors and adherence to treatment in ischemic heart disease António Dias, Carlos Pereira, João Duarte, Madalena Cunha, Daniel Silva O123 Can religiosity improve optimism in participants in states of illness, when controlling for life satisfaction? Lisete M. Mónico, Valentim R. Alferes, Mª São João Brêda, Carla Carvalho, Pedro M. Parreira O124 Empowerment, knowledge and quality of life of people with diabetes type 2 in the Alto Minho Health Local Unit Mª Carminda Morais, Pedro Ferreira, Rui Pimenta, José Boavida O125 Antihypertensive therapy adherence among hypertensive patients from Bragança county, Portugal Isabel C. Pinto, Tânia Pires, Catarina Silva O126 Subjective perception of sexual achievement - An exploratory study on people with overweight Maria Ribeiro, Maria Viega-Branco, Filomena Pereira, Ana Mª Pereira O127 Physical activity level and associated factors in hypertensive individuals registered in the family health strategy of a basic health unit from the city of Palhoça, Santa Catarina, Brazil Fabrícia M. Almeida, Gustavo L. Estevez, Sandra Ribeiro, Marcia R. Kretzer O128 Perception of functional fitness and health in non-institutionalised elderly from rural areas Paulo V. João, Paulo Nogueira, Sandra Novais, Ana Pereira, Lara Carneiro, Maria Mota O129 Medication adherence in patients with type 2 diabetes mellitus treated at primary health care in Coimbra Rui Cruz, Luiz Santiago, Carlos Fontes-Ribeiro O130 Multivariate association between body mass index and multi-comorbidities in elderly people living in low socio-economic status context Guilherme Furtado, Saulo V. Rocha, André P. Coutinho, João S. Neto, Lélia R. Vasconcelos, Nelba R. Souza, Estélio Dantas O131 Metacognition, rumination and experiential avoidance in Borderline Personality Disorder Alexandra Dinis, Sérgio Carvalho, Paula Castilho, José Pinto-Gouveia O132 Health issues in a vulnerable population: nursing consultation in a public bathhouse in Lisbon Alexandra Sarreira-Santos, Amélia Figueiredo, Lurdes Medeiros-Garcia, Paulo Seabra O133 The perception of quality of life in people with multiple sclerosis accompanied in External Consultation of the Local Health Unit of Alto Minho Rosa Rodrigues, Mª Carminda Morais, Paula O. Fernandes O134 Representation of interaction established between immigrant women and nurse during pregnancy to postpartum, from the perspective of immigrant women Conceição Santiago, Mª Henriqueta Figueiredo, Marta L. Basto O135 Illness perceptions and medication adherence in hypertension Teresa Guimarães, André Coelho, Anabela Graça, Ana M. Silva, Ana R. Fonseca O136 A Portuguese study on adults' intimate partner violence, interpersonal trust and hope Luz Vale-Dias, Bárbara Minas, Graciete Franco-Borges P63 QOL' predictors of people with intellectual disability and general population Cristina Simões, Sofia Santos P64 Content validation of the Communication Disability Profile (CDP) - Portuguese Version Ana Serra, Maria Matos, Luís Jesus P65 Study of biochemical and haematological changes in football players Ana S. Tavares, Ana Almeida, Céu Leitão, Edna Varandas, Renato Abreu, Fernando Bellém P66 Body image dissatisfaction in inflammatory bowel disease: exploring the role of chronic illness-related shame Inês A. Trindade, Cláudia Ferreira, José Pinto-Gouveia, Joana Marta-Simões P67 Obesity and sleep in the adult population - a systematic review Odete Amaral, Cristiana Miranda, Pedro Guimarães, Rodrigo Gonçalves, Nélio Veiga, Carlos Pereira P68 Frequency of daytime sleepiness and obstructive sleep apnea risk in COPD patients Tânia C. Fleig, Elisabete A. San-Martin, Cássia L. Goulart, Paloma B. Schneiders, Natacha F. Miranda, Lisiane L. Carvalho, Andrea G. Silva P69 Working with immigrant-origin clients: discourses and practices of health professionals Joana Topa, Conceição Nogueira, Sofia Neves P70 Systemic Lupus Erythematosus – what are audiovestibular changes? Rita Ventura, Cristina Nazaré P71 Mental disorders in the oldest old: findings from the Portuguese national hospitalization database Daniela Brandão, Alberto Freitas, Óscar Ribeiro, Constança Paúl P72 Recurrence analysis in postural control in children with cerebral palsy Cristiana Mercê, Marco Branco, Pedro Almeida, Daniela Nascimento, Juliana Pereira, David Catela P73 The experience of self-care in the elderly with COPD: contributions to reflect proximity care Helga Rafael P74 Culturally competent nurses: managing unpredictability in clinical practice with immigrants Alcinda C. Reis O137 Paediatric speech and language screening: An instrument for health professionals Ana Mendes, Ana R. Valente, Marisa Lousada O138 Anthropometric and nutritional assessment in bodybuilders Diana Sousa, Ana L. Baltazar, Mª Helena Loureiro O139 Computerized adventitious respiratory sounds in children with lower respiratory tract infections Ana Oliveira, José Aparício, Alda Marques O140 Role of computerized respiratory sounds as a marker in LRTI Alda Marques, Ana Oliveira, Joana Neves, Rodrigo Ayoub O141 Confirmatory factor analysis of the Personal Wellbeing Index in people with chronic kidney disease Luís Sousa, Cristina Marques-Vieira, Sandy Severino, Helena José O142 Phonological awareness skills in school aged children Inês Cadorio, Marisa Lousada O143 Assessment of early memories of warmth and safeness in interaction with peers: its relationship with psychopathology in adolescence Marina Cunha, Diogo Andrade, Ana Galhardo, Margarida Couto O144 The molecular effects induced by single shot irradiation on a diffuse large B cell lymphoma cell line Fernando Mendes, Cátia Domingues, Susann Schukg, Ana M. Abrantes, Ana C. Gonçalves, Tiago Sales, Ricardo Teixo, Rita Silva, Jéssica Estrela, Mafalda Laranjo, João Casalta-Lopes, Clara Rocha, Paulo C. Simões, Ana B. Sarmento-Ribeiro, Mª Filomena Botelho, Manuel S. Rosa O145 Morpho-functional characterization of cardiac chambers by Transthoracic Echocardiography, in young athletes of gymnastics competition Virgínia Fonseca, Diogo Colaço, Vanessa Neves O146 Prevalence of the antibodies of the new histo-blood system – FORS system Carlos Jesus, Camilla Hesse, Clara Rocha, Nádia Osório, Ana Valado, Armando Caseiro, António Gabriel, Lola Svensson, Fernando Mendes, Wafa A. Siba, Cristina Pereira, Jorge Tomaz O147 Assessment of the war-related perceived threat in Portuguese Colonial War Veterans Teresa Carvalho, José Pinto-Gouveia, Marina Cunha O148 Pulse transit time estimation for continuous blood pressure measurement: A comparative study Diana Duarte, Nuno V. Lopes, Rui Fonseca-Pinto O149 Blood pressure assessment during standard clinical manoeuvres: A non-invasive PPT based approach Diana Duarte, Nuno V. Lopes, Rui Fonseca-Pinto O150 Development and initial validation of the Activities and Participation Profile related to Mobility (APPM) Anabela C. Martins O151 MEASYCare-2010 Standard–A geriatric evaluation system in primary health care: Reliability and validity of the latest version in Portugal Piedade Brandão, Laura Martins, Margarida Cardoso O152 Interrater and intrarater reliability and agreement of the range of shoulder flexion in the standing upright position through photographic assessment Nuno Morais, Joana Cruz O153 Three-dimensional biofabrication techniques for tissue regeneration Nuno Alves, Paula Faria, Artur Mateus, Pedro Morouço O154 A new computer tool for biofabrication applied to tissue engineering Nuno Alves, Nelson Ferreira, Artur Mateus, Paula Faria, Pedro Morouço O155 Development and psychometric qualities of a scale to measure the functional independence of adolescents with motor impairment Isabel Malheiro, Filomena Gaspar, Luísa Barros O156 Organizational Trust in Health services: Exploratory and Confirmatory factor analysis of the Organizational Trust Inventory- Short Form (OTI-SF) Pedro Parreira, Andreia Cardoso, Lisete Mónico, Carla Carvalho, Albino Lopes, Anabela Salgueiro-Oliveira O157 Thermal symmetry: An indicator of occupational task asymmetries in physiotherapy Adérito Seixas, Valter Soares, Tiago Dias, Ricardo Vardasca, Joaquim Gabriel, Sandra Rodrigues O158 A study of ICT active monitoring adoption in stroke rehabilitation Hugo Paredes, Arsénio Reis, Sara Marinho, Vítor Filipe, João Barroso O159 Paranoia Checklist (Portuguese Version): Preliminary studies in a mixed sample of patients and healthy controls Carolina Da Motta, Célia B. Carvalho, José Pinto-Gouveia, Ermelindo Peixoto O160 Reliability and validity of the Composite Scale on Morningness: European Portuguese version, in adolescents and young adults Ana A. Gomes, Vanessa Costa, Diana Couto, Daniel R. Marques, José A. Leitão, José Tavares, Maria H. Azevedo, Carlos F. Silva O161 Evaluation scale of patient satisfaction with nursing care: Psychometric properties evaluation João Freitas, Pedro Parreira, João Marôco O162 Impact of fibromyalgia on quality of life: Comparing results from generic instruments and FIQR Miguel A. Garcia-Gordillo, Daniel Collado-Mateo, Gang Chen, Angelo Iezzi, José A. Sala, José A. Parraça, Narcis Gusi O163 Preliminary study of the adaptation and validation of the Rating Scale of Resilient Self: Resilience, self-harm and suicidal ideation in adolescents Jani Sousa, Mariana Marques, Jacinto Jardim, Anabela Pereira, Sónia Simões, Marina Cunha O164 Development of the first pressure ulcer in inpatient setting: Focus on length of stay Pedro Sardo, Jenifer Guedes, João Lindo, Paulo Machado, Elsa Melo O165 Forms of Self-Criticizing and Self-Reassuring Scale: Adaptation and early findings in a sample of Portuguese children Célia B. Carvalho, Joana Benevides, Marina Sousa, Joana Cabral, Carolina Da Motta O166 Predictive ability of the Perinatal Depression Screening and Prevention Tool – Preliminary results of the dimensional approach Ana T. Pereira, Sandra Xavier, Julieta Azevedo, Elisabete Bento, Cristiana Marques, Rosa Carvalho, Mariana Marques, António Macedo O167 Psychometric properties of the BaSIQS-Basic Scale on insomnia symptoms and quality of sleep, in adults and in the elderly Ana M. Silva, Juliana Alves, Ana A. Gomes, Daniel R. Marques, Mª Helena Azevedo, Carlos Silva O168 Enlightening the human decision in health: The skin melanocytic classification challenge Ana Mendes, Huei D. Lee, Newton Spolaôr, Jefferson T. Oliva, Wu F. Chung, Rui Fonseca-Pinto O169 Test-retest reliability household life study and health questionnaire Pomerode (SHIP-BRAZIL) Keila Bairros, Cláudia D. Silva, Clóvis A. Souza, Silvana S. Schroeder O170 Characterization of sun exposure behaviours among medical students from Nova Medical School Elsa Araújo, Helena Monteiro, Ricardo Costa, Sara S. Dias, Jorge Torgal O171 Spirituality in pregnant women Carolina G. Henriques, Luísa Santos, Elisa F. Caceiro, Sónia A. Ramalho O172 Polypharmacy in older patients with cancer Rita Oliveira, Vera Afreixo, João Santos, Priscilla Mota, Agostinho Cruz, Francisco Pimentel O173 Quality of life of caregivers of people with advanced chronic disease: Translation and validation of the quality of life in life threatening illness - family carer version (QOLLTI-C-PT) Rita Marques, Mª Anjos Dixe, Ana Querido, Patrícia Sousa O174 The psychometric properties of the brief Other as Shamer Scale for Children (OAS-C): preliminary validation studies in a sample of Portuguese children Joana Benevides, Carolina Da Motta, Marina Sousa, Suzana N. Caldeira, Célia B. Carvalho O175 Measuring emotional intelligence in health care students – Revalidation of WLEIS-P Ana Querido, Catarina Tomás, Daniel Carvalho, João Gomes, Marina Cordeiro O176 Health indicators in prenatal assistance: The impact of computerization and of under-production in basic health centres Joyce O. Costa, Frederico C. Valim, Lígia C. Ribeiro O177 Hope genogram: Assessment of resources and interaction patterns in the family of the child with cerebral palsy Zaida Charepe, Ana Querido, Mª Henriqueta Figueiredo O178 The influence of childbirth type in postpartum quality of life Priscila S. Aquino, Samila G. Ribeiro, Ana B. Pinheiro, Paula A. Lessa, Mirna F. Oliveira, Luísa S. Brito, Ítalo N. Pinto, Alessandra S. Furtado, Régia B. Castro, Caroline Q. Aquino, Eveliny S. Martins O179 Women's beliefs about pap smear test and cervical cancer: influence of social determinants Ana B Pinheiro, Priscila S. Aquino, Lara L. Oliveira, Patrícia C. Pinheiro, Caroline R. Sousa, Vívien A. Freitas, Tatiane M. Silva, Adman S. Lima, Caroline Q. Aquino, Karizia V. Andrade, Camila A. Oliveira, Eglidia F. Vidal O180 Validity of the Portuguese version of the ASI-3: Is anxiety sensitivity a unidimensional or multidimensional construct? Ana Ganho-Ávila, Mariana Moura-Ramos, Óscar Gonçalves, Jorge Almeida O181 Lifestyles of higher education students: the influence of self-esteem and psychological well-being Armando Silva, Irma Brito, João Amado P75 Assessing the quality of life of persons with significant intellectual disability: Portuguese version of Escala de San Martín António Rodrigo, Sofia Santos, Fernando Gomes P76 Childhood obesity and breastfeeding - A systematic review Marlene C. Rosa, Silvana F. Marques P77 Cross-cultural adaptation of the Foot and Ankle Ability Measure (FAAM) for the Portuguese population Sara Luís, Luís Cavalheiro, Pedro Ferreira, Rui Gonçalves P78 Cross-cultural adaptation of the Patient-Rated Wrist Evaluation score (PRWE) for the Portuguese population Rui S. Lopes, Luís Cavalheiro, Pedro Ferreira, Rui Gonçalves P79 Cross-cultural adaptation of the Myocardial Infraction Dimensional Assessment Scale (MIDAS) for Brazilian Portuguese language Bruno H. Fiorin, Marina S. Santos, Edmar S. Oliveira, Rita L. Moreira, Elizabete A. Oliveira, Braulio L. Filho P80 The revised Portuguese version of the Three-Factor Eating Questionnaire: A confirmatory factor analysis Lara Palmeira, Teresa Garcia, José Pinto-Gouveia, Marina Cunha P81 Assessing weight-related psychological inflexibility: An exploratory factor analysis of the AAQW's Portuguese version Sara Cardoso, Lara Palmeira, Marina Cunha; José Pinto-Gouveia P82 Validation of the Body Appreciation Scale-2 for Portuguese women Joana Marta-Simões, Ana L. Mendes, Inês A. Trindade, Sara Oliveira, Cláudia Ferreira P83 The Portuguese validation of the Dietary Intent Scale Ana L. Mendes, Joana Marta-Simões, Inês A. Trindade, Cláudia Ferreira P84 Construction and validation of the Inventory of Marital Violence (IVC) Filipe Nave P85 Portable continuous blood pressure monitor system Mariana Campos, Iris Gaudêncio, Fernando Martins, Lino Ferreira, Nuno Lopes, Rui Fonseca-Pinto P86 Construction and validation of the Scale of Perception of the Difficulties in Caring for the Elderly (SPDCE) Rogério Rodrigues, Zaida Azeredo, Corália Vicente P87 Development and validation of a comfort rating scale for the elderly hospitalized with chronic illness Joana Silva, Patrícia Sousa, Rita Marques P88 Construction and validation of the Postpartum Paternal Quality of Life Questionnaire (PP-QOL) Isabel Mendes, Rogério Rodrigues, Zaida Azeredo, Corália Vicente P89 Infrared thermal imaging: A tool for assessing diabetic foot ulcers Ricardo Vardasca, Ana R. Marques, Adérito Seixas, Rui Carvalho, Joaquim Gabriel P90 Pressure ulcers in an intensive care unit: An experience report Paulo P. Ferreira, Michelle T. Oliveira, Anderson R. Sousa, Ana S. Maia, Sebastião T. Oliveira, Pablo O. Costa, Maiza M. Silva P91 Validation of figures used in evocations: instrument to capture representations Cristina Arreguy-Sena, Nathália Alvarenga-Martins, Paulo F. Pinto, Denize C. Oliveira, Pedro D. Parreira, Antônio T. Gomes, Luciene M. Braga P92 Telephone assistance to decrease burden in informal caregivers of stroke older people: Monitoring and diagnostic evaluation Odete Araújo, Isabel Lage, José Cabrita, Laetitia Teixeira P93 Hope of informal caregivers of people with chronic and advanced disease Rita Marques, Mª Anjos Dixe, Ana Querido, Patrícia Sousa P94 Functionality and quality information from the Portuguese National Epidemiological Surveillance System Sara Silva, Eugénio Cordeiro, João Pimentel P95 Resting metabolic rate objectively measured vs. Harris and Benedict formula Vera Ferro-Lebres, Juliana A. Souza, Mariline Tavares O182 Characteristics of non-urgent patients: Cross-sectional study of an emergency department Mª Anjos Dixe, Pedro Sousa, Rui Passadouro, Teresa Peralta, Carlos Ferreira, Georgina Lourenço O183 Physical fitness and health in children of the 1st Cycle of Education João Serrano, João Petrica, Rui Paulo, Samuel Honório, Pedro Mendes O184 The impact of physical activity on sleep quality, in children Alexandra Simões, Lucinda Carvalho, Alexandre Pereira O185 What is the potential for using Information and Communication Technologies in Arterial Hypertension self-management? Sara Silva, Paulino Sousa, José M. Padilha O186 Exploring psychosocial factors associated with risk of falling in older patients undergoing haemodialysis Daniela Figueiredo, Carolina Valente, Alda Marques O187 Development of pressure ulcers on the face in patients undergoing non-invasive ventilation Patrícia Ribas, Joana Sousa, Frederico Brandão, Cesar Sousa, Matilde Martins O188 The elder hospitalized: Limiting factors of comfort Patrícia Sousa, Rita Marques O189 Physical activity and health state self-perception by Portuguese adults Francisco Mendes, Rosina Fernandes, Emília Martins, Cátia Magalhães, Patrícia Araújo O190 Satisfaction with social support in the elderly of the district of Bragança Carla Grande, Mª Augusta Mata, Juan G. Vieitez O191 Prevalence of death by traumatic brain injury and associated factors in intensive care unit of a general hospital, Brazil Bruna Bianchini, Nazare Nazario, João G. Filho, Marcia Kretzer O192 Relation between family caregivers burden and health status of elderly dependents Tânia Costa, Armando Almeida, Gabriel Baffour O193 Phenomena sensitive to nursing care in day centre Armando Almeida, Tânia Costa, Gabriel Baffour O194 Frailty: what do the elderly think? Zaida Azeredo, Carlos Laranjeira, Magda Guerra, Ana P. Barbeiro O195 The therapeutic self-care as a nursing-sensitive outcome: A correlational study Regina Ferreira O196 Phonetic-phonological acquisition for the European Portuguese from 18 months to 6 years and 12 months Sara Lopes, Liliana Nunes, Ana Mendes O197 Quality of life of patients undergoing liver transplant surgery Julian Martins, Dulcineia Schneider, Marcia Kretzer, Flávio Magajewski O198 Professional competences in health: views of older people from different European Countries Célia Soares, António Marques O199 Life satisfaction of working adults due to the number of hours of weekly exercise Marco Batista, Ruth J. Castuera, Helena Mesquita, António Faustino, Jorge Santos, Samuel Honório O200 Therapeutic itinerary of women with breast cancer in Santa Maria City/RS Betina P. Vizzotto, Leticia Frigo, Hedioneia F. Pivetta O201 The breastfeeding prevalence at 4 months: Maternal experience as a determining factor Dolores Sardo O202 The impact of the transition to parenthood in health and well-being Cristina Martins, Wilson Abreu, Mª Céu Figueiredo P96 Self-determined motivation and well-being in Portuguese active adults of both genders Marco Batista, Ruth Jimenez-Castuera, João Petrica, João Serrano, Samuel Honório, Rui Paulo, Pedro Mendes P97 The geriatric care: ways and means of comforting Patrícia Sousa, Rita Marques P98 The influence of relative age, subcutaneous adiposity and physical growth on Castelo Branco under-15 soccer players 2015 António Faustino, Paulo Silveira, João Serrano, Rui Paulo, Pedro Mendes, Samuel Honório P99 Data for the diagnostic process focused on self-care – managing medication regime: An integrative literature review Catarina Oliveira, Fernanda Bastos, Inês Cruz P100 Art therapy as mental health promotion for children Cláudia K. Rodriguez, Márcia R. Kretzer, Nazaré O. Nazário P101 Chemical characterization of fungal chitosan for industrial applications Pedro Cruz, Daniela C. Vaz, Rui B. Ruben, Francisco Avelelas, Susana Silva, Mª Jorge Campos P102 The impact of caring older people at home Maria Almeida, Liliana Gonçalves, Lígia Antunes P103 Development of the first pressure ulcer in an inpatient setting: Focus on patients' characteristics Pedro Sardo, Jenifer Guedes, João Simões, Paulo Machado, Elsa Melo P104 Association between General Self-efficacy and Physical Activity among Adolescents Susana Cardoso, Osvaldo Santos, Carla Nunes, Isabel Loureiro O203 Characterization of the habits of online acquisition of medicinal products in Portugal Flávia Santos, Gilberto Alves O204 Waiting room – A space for health education Cláudia Soar, Teresa O. Marsi O205 Safey culture evaluation in hospitalized children Ernestina Silva, Dora Pedrosa, Andrea Leça, Daniel Silva O206 Sexual Self-awareness and Body Image Ana Galvão, Maria Gomes, Paula Fernandes, Ana Noné O207 Perception of a Portuguese population regarding the acquisition and consumption of functional foods Jaime Combadão, Cátia Ramalhete, Paulo Figueiredo, Patrícia Caeiro O208 The work process in primary health care: evaluation in municipalities of southern Brazil Karine C. Fontana, Josimari T. Lacerda, Patrícia O. Machado O209 Exploration and evaluation of potential probiotic lactic acid bacteria isolated from Amazon buffalo milk Raphaelle Borges, Flávio Barbosa, Dayse Sá O210 Road safety for children: Using children's observation, as a passenger Germana Brunhoso, Graça Aparício, Amâncio Carvalho O211 Perception and application of quality-by-design by the Pharmaceutical industry in Portugal Ana P. Garcia, Paula O. Fernandes, Adriana Santos O212 Oral health among Portuguese children and adolescents: a public health issue Nélio Veiga, Carina Brás, Inês Carvalho, Joana Batalha, Margarida Glória, Filipa Bexiga, Inês Coelho, Odete Amaral, Carlos Pereira O213 Plant species as a medicinal resource in Igatu-Chapada Diamantina (Bahia, Brazil) Cláudia Pinho, Nilson Paraíso, Ana I. Oliveira, Cristóvão F. Lima, Alberto P. Dias O214 Characterization of cognitive and functional performance in everyday tasks: Implications for health in institutionalised older adults Pedro Silva, Mário Espada, Mário Marques, Ana Pereira O215 BMI and the perception of the importance given to sexuality in obese and overweight people Ana Mª Pereira, Mª Veiga-Branco, Filomena Pereira, Maria Ribeiro O216 Analysis and comparison of microbiological contaminations of two different composition pacifiers Vera Lima, Ana I. Oliveira, Cláudia Pinho, Graça Cruz, Rita F. Oliveira, Luísa Barreiros, Fernando Moreira O217 Experiences of couple relationships in the transition to retirement Ana Camarneiro, Mª Helena Loureiro, Margarida Silva O218 Preventive and corrective treatment of drug-induced calcium deficiency: an analysis in a community pharmacy setting Catarina Duarte, Ângelo Jesus, Agostinho Cruz O219 Profile of mood states in physically active elderly subjects: Is there a relation with health perception? Maria Mota, Sandra Novais, Paulo Nogueira, Ana Pereira, Lara Carneiro, Paulo V. João O220 (Un)Safety behaviour at work: the role of education towards a health and safety culture Teresa Maneca Lima O221 Analysis of the entrepreneurial profile of students attending higher education in Portugal: the Carland Entrepreneurship Index application Anabela Salgueiro-Oliveira, Marina Vaquinhas, Pedro Parreira, Rosa Melo, João Graveto, Amélia Castilho, José H. Gomes O222 Evaluation of welfare and quality of life of pregnant working women regarding the age of the pregnant María S. Medina, Valeriana G. Blanco O223 Psychological wellbeing protection among unemployed and temporary workers: Uncovering effective community-based interventions with a Delphi panel Osvaldo Santos, Elisa Lopes, Ana Virgolino, Alexandra Dinis, Sara Ambrósio, Inês Almeida, Tatiana Marques, Mª João Heitor O224 Chilean population norms derived from the Health-related quality of life SF-6D Miguel A. Garcia-Gordillo, Daniel Collado-Mateo, Pedro R. Olivares, José A. Parraça, José A. Sala O225 Motivation of college students toward Entrepreneurship: The influence of social and economic instability Amélia Castilho, João Graveto, Pedro Parreira, Anabela Oliveira, José H. Gomes, Rosa Melo, Marina Vaquinhas O226 Use of aromatic and medicinal plants, drugs and herbal products in Bragança city Mónia Cheio, Agostinho Cruz, Olívia R. Pereira O227 Edible flowers as new novel foods concept for health promotion Sara Pinto, Adriana Oliveira, M. Conceição Manso, Carla Sousa, Ana F. Vinha O228 The influence of leisure activities on the health and welfare of older people living in nursing homes Mª Manuela Machado, Margarida Vieira O229 Risk of falling, fear of falling and functionality in community-dwelling older adults Beatriz Fernandes, Teresa Tomás, Diogo Quirino O230 Musculoskeletal pain and postural habits in children and teenage students Gustavo Desouzart, Rui Matos, Magali Bordini, Pedro Mouroço O231 What's different in Southern Europe? The question of citizens' participation in health systems Ana R. Matos, Mauro Serapioni O232 Occupational stress in Portuguese police officers Teresa Guimarães, Virgínia Fonseca, André Costa, João Ribeiro, João Lobato O233 Is occupational therapy culturally relevant to promote mental health in Burkina Faso? Inmaculada Z. Martin, Anita Björklund P105 Pay-for-performance satisfaction and quality in primary care Aida I. Tavares, Pedro Ferreira, Rui Passadouro P106 Economic development through life expectancy lenses Sónia Morgado P107 What is the effectiveness of exercise on smoking cessation to prevent clinical complications of smoking? Nuno Tavares, João Valente, Anabela C. Martins P108 A systematic review of the effects of yoga on mental health Patrícia Araújo, Rosina Fernandes, Francisco Mendes, Cátia Magalhães, Emília Martins P109 Healthy lifestyle: comparison between higher education students that lived until adult age in rural and urban environment Pedro Mendes, Rui Paulo, António Faustino, Helena Mesquita, Samuel Honório, Marco Batista P110 Evaluation of the Mobile Emergency Care Service (SAMU) in Brazil Josimari T. Lacerda, Angela B. Ortiga, Mª Cristina Calvo, Sônia Natal P111 Bioactive compounds - antioxidant activity of tropical fruits Marta Pereira P112 Use of non-pharmacological methods to relieve pain in labour Manuela Ferreira, Ana R. Prata, Paula Nelas, João Duarte P113 Mechanical safety of pacifiers sold in Portuguese pharmacies and childcare stores Juliana Carneiro, Ana I. Oliveira, Cláudia Pinho, Cristina Couto, Rita F. Oliveira, Fernando Moreira P114 The importance of prenatal consultation: Information to pregnant women given on a unit of primary care Ana S. Maia, Michelle T. Oliveira, Anderson R. Sousa, Paulo P. Ferreira, Géssica M. Souza, Lívia F. Almada, Milena A. Conceição, Eujcely C. Santiago P115 Influence of different backpack loading conditions on neck and lumbar muscles activity of elementary school children Sandra Rodrigues, Gabriela Domingues, Irina Ferreira, Luís Faria, Adérito Seixas P116 Efficacy and safety of dry extract Hedera helix in the treatment of productive cough Ana R. Costa, Ângelo Jesus, Américo Cardoso, Alexandra Meireles, Armanda Colaço, Agostinho Cruz P117 A portrait of the evaluation processes of education groups in primary health care Viviane L. Vieira, Kellem R. Vincha, Ana Mª Cervato-Mancuso P118 Benefits of vitamins C and E in sensorineural hearing loss: a review Melissa Faria, Cláudia Reis P119 BODY SNAPSHOT – a web-integrated anthropometric evaluation system Marco P. Cova, Rita T. Ascenso, Henrique A. Almeida, Eunice G. Oliveira P120 Anthropometric evaluation and variation during pregnancy Miguel Santana, Rafael Pereira, Eunice G. Oliveira, Henrique A. Almeida, Rita T. Ascenso P121 Knowledge of college students on the amendments of their eating habits and physical activity index in the transition to higher education Rita Jesus, Rodrigo Tapadas, Carolina Tim-Tim, Catarina Cezanne, Matilde Lagoa, Sara S. Dias, Jorge Torgal P122 Muscular activity of a rally race car driver João Lopes, Henrique Almeida, Sandra Amado, Luís Carrão O234 Literacy and results in health Madalena Cunha, Luís Saboga-Nunes, Carlos Albuquerque, Olivério Ribeiro O235 Literacy promotion and empowerment of type 2 diabetics elderly in four family health units of the group of health centers of Dão Lafões Suzete Oliveira, Mª Carminda Morais O236 Mediterranean diet, health and life quality among Portuguese children Emília Martins, Francisco Mendes, Rosina Fernandes, Cátia Magalhães, Patrícia Araújo O237 Health literacy, from data to action - translation, validation and application of the European Health Literacy Survey in Portugal (HLS-EU-PT) Ana R. Pedro, Odete Amaral, Ana Escoval O238 Oral health literacy evaluation in a Portuguese military population Victor Assunção, Henrique Luís, Luís Luís O239 Preferences to Internet-based cognitive behavioural therapy – do attachment orientations matter? Jennifer Apolinário-Hagen, Viktor Vehreschild O240 A comparative transnational study in health literacy between Austria and Portugal Ulrike Fotschl, Gerald Lirk, Anabela C. Martins, Isabel Andrade, Fernando Mendes O241 Health literacy and social behaviours: relationship with sexually transmitted diseases? Verónica Mendonça, Sandra Antunes, Isabel Andrade, Nádia Osório, Ana Valado, Armando Caseiro, António Gabriel, Anabela C. Martins, Fernando Mendes O242 Parenting styles and attachment to parents: what relationships? Paula A. Silva, Lisete M. Mónico, Pedro M. Parreira, Carla Carvalho O243 Work-life balance in health professionals and professors: comparative study of workers with shift work and fixed schedule Carla Carvalho, Pedro M. Parreira, Lisete M. Mónico, Joana Ruivo O244 Technology literacy in self-management of diabetes Vânia Silva, Paulino Sousa, José M. Padilha O245 Satisfaction with therapeutic education and its relationship with clinical variables in children with type 1 diabetes Vera Ferraz, Graça Aparício, João Duarte O246 Nutrition-related knowledge in middle-age and older patients with type 2 diabetes Carlos Vasconcelos, António Almeida, Joel Neves, Telma Correia, Helena Amorim, Romeu Mendes O247 Validating the HLS-EU-(PT) questionnaire to measure health literacy in adolescents (CrAdLiSa project: HLS-EU-PT) Luís Saboga-Nunes, Madalena Cunha, Carlos Albuquerque O248 Health education in people with coronary heart disease: Experience of the cardiology department of a hospital on the outskirts of Lisbon Elsa S. Pereira, Leonino S. Santos, Ana S. Reis, Helena R. Silva, João Rombo, Jorge C. Fernandes, Patrícia Fernandes O249 Information and training needs of informal caregivers of individuals with stroke sequelae: a qualitative survey Jaime Ribeiro, Catarina Mangas, Ana Freire O250 Prevention of psychoactive substances consumption in students from 6th grade of Albergaria-a-Velha´s School Group Sara Silva, Irene Francisco, Ana Oliveira O251 Promoting healthy sexuality: shared responsibility for family, youth and educators Helena Catarino, Mª Anjos Dixe, Mª Clarisse Louro O252 Sexual risk behaviour in adolescents and young people Saudade Lopes, Anjos Dixe O253 Knowledge of school staff on type 1 diabetes Mª Anjos Dixe, Eva Menino, Helena Catarino, Fátima Soares, Ana P. Oliveira, Sara Gordo, Teresa Kraus O254 Sexual health in adolescents: the impact of information search in literacy Catarina Tomás, Paulo Queirós, Teresa Rodrigues P123 Improving basic life support skills in adolescents through a training programme Pedro Sousa, João G. Frade, Catarina Lobão P124 Difficulties in sexual education reported by basic education teachers in the city of Foz do Iguaçu - Brazil Cynthia B. Moura, Laysa C. Dreyer, Vanize Meneghetti, Priscila P. Cabral P125 Breast cancer survivors: subjects and resources for information. A qualitative systematic review Francisca Pinto, Paulino Sousa, Mª Raquel Esteves P126 Relationship between health literacy and prevalence of STI in Biomedical Laboratory Science students Sofia Galvão, Ite Tytgat, Isabel Andrade, Nádia Osório, Ana Valado, Armando Caseiro, António Gabriel, Anabela C. Martins, Fernando Mendes P127 Health literacy, risk behaviours and sexually transmitted diseases among blood donors Mónica Casas-Novas, Helena Bernardo, Isabel Andrade, Gracinda Sousa, Ana P. Sousa, Clara Rocha, Pedro Belo, Nádia Osório, Ana Valado, Armando Caseiro, António Gabriel, Anabela C. Martins, Fernando Mendes P128 Promoting literacy in pregnancy health-care Fátima Martins, Montserrat Pulido-Fuentes P129 The lifestyles of the operating assistants of education Isabel Barroso, Gil Cabral, M. João Monteiro, Conceição Rainho P130 Experiences of service-learning health and the literary art: reflections about the health education Alessandro Prado, Yara M. Carvalho P131 Life long swimming – a European Erasmus + project Maria Campos, Liliana Moreira, José Ferreira, Ana Teixeira, Luís Rama